2010
DOI: 10.1542/peds.2010-1129
|View full text |Cite
|
Sign up to set email alerts
|

Left Vocal Cord Paralysis After Extreme Preterm Birth, a New Clinical Scenario in Adults

Abstract: LVCP is not uncommon in young adults exposed to PDA surgery as preterm infants. The condition may be overlooked easily, and symptoms may be confused with those of other diseases. Laryngoscopy should be offered on the basis of liberal indications after PDA ligation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 126 publications
4
58
0
Order By: Relevance
“…Thirty-two studies that satisfied the inclusion criteria were included in the analysis (Fig 1). OCEBM levels of evidence varied from level 3 (9 studies) [9][10][11][14][15][16]20,23,26 to level 4 (23 studies) [6][7][8]12,13,[17][18][19]21,22,24,25,[27][28][29][30][31][32][33][34][35][36][37] ( Table 1). Occurrence of UVFP, type of surgery, patient demographics, and vocal fold assessment are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two studies that satisfied the inclusion criteria were included in the analysis (Fig 1). OCEBM levels of evidence varied from level 3 (9 studies) [9][10][11][14][15][16]20,23,26 to level 4 (23 studies) [6][7][8]12,13,[17][18][19]21,22,24,25,[27][28][29][30][31][32][33][34][35][36][37] ( Table 1). Occurrence of UVFP, type of surgery, patient demographics, and vocal fold assessment are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,[10][11][12][13][14][15]17,20,21,24,[27][28][29][30][31][34][35][36][37] The weighted pooled proportion was 8.7% (95% CI, 5.4% to 12.6%) (Fig 3). Heterogeneity analysis measured an I 2 of 81.6% (95% CI, 65.0% to 88.4%).…”
Section: Analysis By Type Of Surgerymentioning
confidence: 99%
“…Totally 50 reported were collected, including 19 (38%) case reports or case series [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], 1 (2%) technique [30], 17 (34%) retrospective [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 13 (26%) prospective reports [7,11,[49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…The intraoperative damage to the left recurrent laryngeal nerve along its course around the PDA during the dissection of the nerve might result in stretch injury [55]. Røksund et al [11] found that infants with left vocal cord paralysis had a lower birth weight, longer duration of ventilation, and the greater proportion with bronchopulmonary dysplasia. Smith et al [58] noted that infants < 30 weeks postmenstrual age and/or body weight < 1,250 g at PDA ligation were at the highest risk, with an incidence of left vocal cord paralysis of 25%.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation